Hipertensi Care: An Android-Based Mobile Application Integrating Acupressure, Progressive Muscle Relaxation, and Blood Pressure Monitoring - Kusuma, I Made Jaya; Suyasa, I Gede Putu Darma; Wulandari, Sarah Kartika (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Hypertension remains a major public health concern, contributing to long-term healthcare costs and complications such as stroke and kidney failure. Although pharmacological therapy is essential, patient adherence to lifestyle-based approaches remains limited. Evidence demonstrates that acupressure and Progressive Muscle Relaxation (PMR) can lower blood pressure. However, no digital platform has integrated both interventions into a single self-management tool. This Research and Development (R&D) study developed an Android-based mobile application, Hipertensi Care, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to support hypertension self- management. The Analysis phase included a literature review, needs assessment, and Focus Group Discussions (FGDs) with 10 participants to identify user requirements. The Design phase involved creating the application workflow, interface, and evidence-based educational content. During Development, the application underwent content validation by 7 experts (three nurses, two acupuncturists, one cardiovascular internist, and one media specialist). A limited trial with 35 individuals with hypertension was conducted in the Implementation phase. Usability and user acceptance were evaluated using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). The results showed excellent usability, high perceived usefulness and ease of use, and positive user experience across all UEQ dimensions. Overall, Hipertensi Care demonstrated strong alignment with user needs for hypertension self-management and is ready to progress to effectiveness testing to assess its impact on blood pressure and related clinical outcomes.